Moderasi dan Dakwah: Gaya Kepemimpinan Inklusif Sultan Maulana Hasanuddin: Moderasi dan dakwah - Farhan Shirath; Zaimudin; Iin Kandedes (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the relationship between moderation and da’wah through the inclusive leadership style of Sultan Maulana Hasanuddin using a literature study approach. Sultan Maulana Hasanuddin is recognized as an important figure in the spread of Islam in Banten who implemented peaceful, open, and unity-oriented da’wah strategies. The research method employed in this study is library research by examining historical literature, books, scientific articles, and documents related to Islamic leadership and the development of da’wah during the Banten Sultanate period. The findings indicate that Sultan Maulana Hasanuddin’s leadership style reflected the values of Islamic moderation emphasizing tolerance, justice, cultural dialogue, and respect for social diversity. In conducting da’wah activities, he did not apply coercive methods but prioritized persuasive approaches through education, trade, social relations, and the establishment of religious institutions. This inclusive leadership successfully created social stability and strengthened public acceptance of Islamic teachings without eliminating local cultural identity. Furthermore, the moderate approach implemented by the Sultan contributed to harmonious relations among communities with different backgrounds. This study concludes that the leadership of Sultan Maulana Hasanuddin can serve as a model for the development of moderate da’wah in the modern era, especially in addressing challenges related to intolerance and religious social conflict. The values of inclusiveness, wisdom, and humanistic approaches practiced by the Sultan remain relevant as a foundation for building peaceful, tolerant, and harmonious societies within multicultural and multireligious environments.